Synthesis of CaWO4, SrWO4 and BaWO4 with nanosized particles using cyclic microwave radiation - Titipun Thongtem (2018)
Scheelite tungstates (MWO4, M = Ca, Sr and Ba) were successfully synthesized by the reactions of M(NO3)2 · 2H 2O and Na2WO4-2H2O in propylene glycol and NaOH using cyclic microwave radiation. The tungstates were detected using SAED. TEM and SEM analyses revealed the presence of dispersed nanosized particles for CaWO4, nanosized particles in irregular clusters for SrWO4, and nanosized particles in clusters shaped like dumb-bells for BaWO4. Raman spectra provide evidence of the scheelite structure with six different vibration modes. Arrays of crystallographic planes were detected using HRTEM. PL emission of the products is caused by the 1T2 → 1A1 transition of electrons within [WO4]2- tetrahedrons in the blue spectral region at 407-419 nm.